The Influence of Majelis Taklim Activities on Religious Literacy of Adolescents in the Imam Syafi'i Mosque Environment in Sampit - Edo Ferdian; Malik Ashari; Syamsul Arifin; Benny Prasetiya (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2026)
This study aims to analyze the influence of majelis taklim activities on adolescent religious literacy in the Imam Syafi'i Mosque environment in Sampit. The urgency of the study is based on the need to strengthen adolescent religious literacy in the digital era characterized by the rapid flow of religious information with varying quality and authority, so that a structured and credible development space is needed through mosque-based non-formal Islamic education. The study used a quantitative approach with a correlational survey design. The study population was all adolescents in the Imam Syafi'i Mosque environment in Sampit, with a sample of 41 valid respondents determined through probability sampling (simple random sampling). Data were collected using a five-point Likert scale questionnaire, then analyzed with descriptive statistics and simple linear regression using SPSS. The results showed that the level of adolescent participation in majelis taklim activities was in the high category (M = 41.58; SD = 7.06), while adolescent religious literacy was in the good to very good category (M = 79.54; SD = 13.39). Regression tests show that majelis taklim activities have a positive and significant effect on adolescent religious literacy (β = 1.833; p < 0.05) with a coefficient of determination R² = 0.935, meaning that 93.5% of the variation in religious literacy can be explained by majelis taklim activities. This finding confirms that majelis taklim plays a role not only as a forum for religious study, but also as an effective educational space in transmitting knowledge and strengthening the internalization of adolescent religious values.